Towards a programming language based on Prior's metric temporal operators - Cobo, María Laura (2000)
Many different areas in Computer Science - like Real Time Systems, Temporal Data Bases, Program Verification and Multimedia-demandan adequate way to represent and use the notions of time and change. We present a programming language which is defined starting from a metric temporallogic previously considered by Prior and Rescher ([Pri67a], [Res66]). The language is based on the declarative approach and combines temporal operators to represent order notions with the capability to refer to distance notions. These features provide a very useful tool to handle practical situations with a formal and clear theoretical basement. We provide an algorithm for the implementation of an interpreter of this language, based on the notion of a labelled computation tree [ Gab87]. It can be shown that all queries lead to finite computations. Sorne examples are included to illustrate its behaviour.